KONSERVASI ENERGI PADA GEDUNG KANTOR SEKRETARIAT DAERAH KOTA DENPASAR - Gde Wikan Pradnya Dana; I Gede Dyana Arjana; Cok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2020)
Regional Secretariat Building Denpasar in 2017 experienced a separation in two parts.The separation resulted in the empty room, even though are empty room turned out toconsumption building power in 2018 continued to experience enchancement. The study hasbeen done there is the room that has the intensity of energy consumption which do not comptywith SNI. Solutions that can be given is to replace the type of split standard air conditioner (AC)into a type of low watt air conditioner (AC). Replacement type split standard air conditioner (AC)1,5 PK became type of low watt air conditioner (AC) 1,5 PK can make saving of up 11,62 % orRp 21.068.468,00. Saving electric energy consumption on lighting system can be done byinstalling an automatic switch with time or by using an a light sensor system.